2007
DOI: 10.1016/j.neuroimage.2007.01.028
|View full text |Cite
|
Sign up to set email alerts
|

A tensor based morphometry study of longitudinal gray matter contraction in FTD

Abstract: Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by progressive behavioural abnormalities and frontotemporal atrophy. Here we used tensor based morphometry (TBM) to identify regions of longitudinal progression of gray matter atrophy in FTD compared to controls. T1-weighted MRI images were acquired at presentation and 1-year follow-up from 12 patients with mild to moderate FTD and 12 healthy controls. Using TBM as implemented in SPM2, a voxel-wise estimation of regional tissue volume c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 37 publications
5
60
2
2
Order By: Relevance
“…TBM is a recently introduced technique that was successful at identifying patterns of atrophy progression typical of various neurodegenerative disorders (Brambati et al, 2007;Chan et al, 2001a,b;Fox et al, 2000Fox et al, , 2001Fox et al, , 1999Fox and Freeborough, 1997;Freeborough et al, 1996;Kipps et al, 2005;Leow et al, 2006;Studholme et al, 2001), including classic SD (Cardenas and Studholme, 2004;Whitwell et al, 2004). Here, we showed that the automated, whole-brain TBM technique as implemented in SPM, could detect differential patterns of longitudinal gray matter atrophy in two variants of the same disease.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…TBM is a recently introduced technique that was successful at identifying patterns of atrophy progression typical of various neurodegenerative disorders (Brambati et al, 2007;Chan et al, 2001a,b;Fox et al, 2000Fox et al, , 2001Fox et al, , 1999Fox and Freeborough, 1997;Freeborough et al, 1996;Kipps et al, 2005;Leow et al, 2006;Studholme et al, 2001), including classic SD (Cardenas and Studholme, 2004;Whitwell et al, 2004). Here, we showed that the automated, whole-brain TBM technique as implemented in SPM, could detect differential patterns of longitudinal gray matter atrophy in two variants of the same disease.…”
Section: Discussionmentioning
confidence: 60%
“…Both spatial pre-processing and statistical analysis were implemented in SPM2. Details regarding TBM image pre-processing are described in previous studies (Brambati et al, 2007;Kipps et al, 2005) (Fig. 1).…”
Section: Whole-brain Longitudinal Neuroimaging Analysis: Tensor-basedmentioning
confidence: 99%
“…Depending on the variant of the disease, atrophy associated with FTLD has been described as involving diverse regions of the brain [30,31] . In a recent study using cortical thickness analyses, GM atrophy of the posterior midline cortex was found in FTLD patients [10] , but it was not described in other studies that have applied VBM [32][33][34][35] . Consistent with the latter studies, in the current study significant PREC/PCC atrophy was observed in AD, MCI, and bvFTLD, but not PPA patients.…”
Section: Discussionmentioning
confidence: 95%
“…It has been recently shown that, compared to the traditional volumetric method, TBM yields more statistical power to associate structure with other biological and demographic variables (Lee et al, 2007). It was also demonstrated that the method is well suited to track longitudinal changes of individual brains (e.g., Brambati et al, 2007;Cardenas, Studholme, Gazdzinski, Durazzo, & Meyerhoff, 2007;Leow et al, 2006). Second, to further enhance the accuracy and sensitivity of TBM protocol, a novel algorithm, symmetric normalization (SyN ; Avants, Epstein, Grossman, & Gee, in press;Avants, Schoenemann, & Gee, 2006) was employed for the inter-subject image normalization.…”
Section: Introductionmentioning
confidence: 99%